Development of Tests for Arm Coordination Impairment in Paralympic Classification - Altmann, Viola C.; Hendriks, Nadine; Lammens, Eline A.; Janssen, Mariska (Frontiers in Rehabilitation Sciences, 2022)
Background: In Paralympic sport, classification of impairment with the ability to detect misrepresentation of abilities is mandatory. In wheelchair rugby, there is currently no objective method to classify arm coordination impairment. In previous research, sufficient correlation between the spiral test (ST) and activity in wheelchair rugby was found in athletes with coordination impairment. However the ST depends on maximum voluntary effort. Purpose: To assess if the ST is an objective test for arm coordination impairment in which maximum voluntary effort can be distinguished from intentional misrepresentation. To elaborate this, the aims of this study were to 1) assess the test-retest reliability of the ST and 2) assess if Fitts’s law is applicable to the ST. Methods: Nineteen volunteers without impairments performed two sessions with three STs per arm. The STs were projected and measured on a tablet and had three different indices of difficulty based on differences in spiral width. The time to complete the spiral was measured and a penalty time was added for each time the borderline of the spiral was touched (3 s) or crossed (5 s). Results: Test-retest reliability was assessed using a Bland-Altman analysis and showed limits of agreement that were wider than the margins of 2SD from the group mean. Repeated measurement correlation coefficients between the index of difficulty according to Fitts’s law and the movement time was 0.95 (p-value<0.001) for both test and retest. A post-hoc optimisation of penalty times revealed an optimum penalty time of 2.0 s for the dominant arm and 2.5 for the non-dominant arm for any contact with the margins of the spiral. Conclusions: The ST has sufficient test-retest reliability and Fitts’s law is applicable. Therefore, it is a promising option for classification of arm coordination impairment with the option to distinguish intentional misrepresentation from maximum voluntary effort.